KEKERASAN DAN KEJAHATAN SEKSUAL PADA PEREMPUAN DALAM PERSPEKTIF KEJAHATAN KEMANUSIAAN - Shadrina Khairunnisa Oli'i; Wayu Donri (Jurnal Ilmiah Wahana Pendidikan, 2023)
Cases of sexual violence and sexual crimes, which until now are still increasing, have become a complicated and very important issue of all crimes experienced by women. This is because the problem regarding this case has its own dimensions which are very specific to women who act as victims. In cases of sexual violence that occurred, many of the victims' rights were violated, for example, the right not to become a target of crime, the right to security, and others. The purpose of this research is to find out about violence and sexual crimes based on the perspective of crimes against humanity. This study uses a qualitative research method that is specific to data collection through library research. The results of this study indicate that cases of violence and sexual crimes against women, regardless of the form and form of their actions, are crimes against humanity that are contrary to human rights. As for predictions of alternative solutions to cases of violence and sexual crimes in Indonesia, solutions can be made to use a settlement using the family court as has been owned by other countries. Besides that, it can also use alternative settlements using the laws and culture of the local community.